PRE-scripted debriefing for Paediatric simulation Associated with Resuscitation EDucation (PREPARED): A multicentre, cluster randomised controlled trial - Peter J. Snelling; Louise Dodson; Emily Monteagle; Robert S. Ware; Jason Acworth; Ben Symon; Ben Lawton (Resuscitation Plus, 2022)
Aim: Scripted debriefing tools may improve the performance of novices debriefing in resuscitation courses, but this has not previously been measured. The aim of this study was to determine the impact of a script on the quality of debriefs in a statewide paediatric resuscitation course. Methods: This cluster-randomised controlled trial compared scripted debriefing (intervention) versus non-scripted debriefing (control) for participants in a paediatric resuscitation course. The trial was conducted across participating sites in Queensland, Australia, from November 2017 to February 2020. Debriefing quality was measured using the Observational Structured Assessment of Debriefing (OSAD) tool. The OSAD tool rates 8 domains that comprise the elements of an ideal debrief. OSAD scores between scripted and non-scripted groups were compared, overall and after stratification by debriefer experience and site size. Results: Seventy debriefings occurred across 19 sites (intervention, n = 34, control n = 36). There was a statistically significant increase in total OSAD scores in the scripted group, compared to non-scripted (mean difference (MD) = 3.5, 95% confidence interval (CI) 0.7–6.2, p = 0.01). The categories of ‘reflection’ and ‘analysis’ had the greatest difference in OSAD scores in the scripted group (MD = 0.8, 95%CI 0.2–1.3, p = 0.005; MD = 0.6, 95%CI 0.2–1.0, p = 0.007). After stratification, overall OSAD scores improved for novices (MD = 4.1, 95%CI 0.5–7.7, p = 0.03) and large centres (MD = 5.2, 95%CI 1.1–9.2, p = 0.01). Conclusion: Providing debriefing scripts to faculty facilitating simulated paediatric resuscitation scenarios improved the quality of debriefing, especially for novices and those at large sites. The development and provision of debriefing scripts for large-scale paediatric resuscitation courses should be considered.